University proceedings. Volga region. Natural sciences - E.G. Khudonogova; T.A. Khusheyeva (Известия высших учебных заведений. Поволжский регион: Естественные науки)
Background. One of the valuable medicinal plants is Calendula officinalis L. Numerous varieties and forms of Calendula L. have medicinal and ornamental properties. The purpose of the study was to investigate the biomorphological characteristics and productivity of Calendula raw materials in the Cis-Baikal region. Materials and methods. Varieties with double inflorescences were taken for testing: Calendula Orange King, C. Marigold. C. officinalis served as a control. Wide-row sowing of seeds was carried out on May 11. The experiments were repeated 10 times. Results. Mass emergence of seedlings is observed on May 25–29, the budding phase is May 5–8, the beginning of flowering is June 19–27, mass flowering occurs June 27 – July 4. The flowering period of the studied species and varieties is very extended, some shoots with buds go under the snow, not having time to open some of them. The largest number of buds that have not blossomed by September 25 was noted in the Orange King variety, the buds of this variety are large and form more slowly compared to the Marigold variety of calendula and C. officinalis. Conclusions. The optimal time for sowing Calendula seeds, in the conditions of the Cis-Baikal region, is the beginning of May (May 1–11), later sowing of seeds (May 20) leads to late flowering of plants, a delay in the opening of buds and a decrease in the yield of raw inflorescences. The yield of raw materials depends on the height of the plants, the number of lateral shoots with inflorescences, the number of blossomed buds and the diameter of the inflorescences. The lowergrowing C. officinalis and C. Orange King form a significant number of lateral shoots with inflorescences. The most productive is the Orange King variety. The use of humates increases the yield of Calendula raw materials by 1,1–1,5 times, while the content of chemical elements, except for iron, corresponds to the maximum permissible concentrations in medicinal raw materials. The highest level of carotenoids was found in the Orange King variety.